2018
DOI: 10.1002/prp2.437
|View full text |Cite
|
Sign up to set email alerts
|

Dual androgen receptor (AR) and STAT3 inhibition by a compound targeting the AR amino‐terminal domain

Abstract: Prostate cancer (PCa) often recurs as incurable castration‐resistant prostate cancer (CRPC) after the failure of androgen deprivation therapy. CRPC development relies on androgen receptor (AR) signaling. The IL6/STAT3 pathway is also a key driver of CRPC. The crosstalk between IL6/STAT3 and the AR pathways provides opportunities to explore next‐generation agents to treat PCa. Through screening of around 600 natural compounds in our newly established prostate tumorigenesis model, potential STAT3 signaling inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…112 Studies have shown that cinobufagin-3-acetate binds directly to the NTD thus inhibiting AR-STAT3 signaling-a pathway that is a key driver in the progression to CRPC. 113 The compound demonstrated static levels of AR inhibition in the presence of varying concentrations of R1881, discounting a mechanism that functions via the LBP. Cinobufagin-3-acetate displayed significant inhibition against the clinical variants AR-V7 and ARv567es in LNCaP cells at concentrations of 1 and 10 µM, respectively, and was found to reduce AR protein expression without altering AR mRNA levels or reducing AR nuclear translocation.…”
Section: Ntd-targeting Natural Productsmentioning
confidence: 93%
See 1 more Smart Citation
“…112 Studies have shown that cinobufagin-3-acetate binds directly to the NTD thus inhibiting AR-STAT3 signaling-a pathway that is a key driver in the progression to CRPC. 113 The compound demonstrated static levels of AR inhibition in the presence of varying concentrations of R1881, discounting a mechanism that functions via the LBP. Cinobufagin-3-acetate displayed significant inhibition against the clinical variants AR-V7 and ARv567es in LNCaP cells at concentrations of 1 and 10 µM, respectively, and was found to reduce AR protein expression without altering AR mRNA levels or reducing AR nuclear translocation.…”
Section: Ntd-targeting Natural Productsmentioning
confidence: 93%
“…Cinobufagin‐3‐acetate is a steroidal natural product secreted by the asiatic toad, Bufo gargarizans (Figure 16B). 112 Studies have shown that cinobufagin‐3‐acetate binds directly to the NTD thus inhibiting AR‐STAT3 signaling—a pathway that is a key driver in the progression to CRPC 113 . The compound demonstrated static levels of AR inhibition in the presence of varying concentrations of R1881, discounting a mechanism that functions via the LBP.…”
Section: Targeting the Ntdmentioning
confidence: 99%
“…Subsequently, STAT3 activity increases AR recruitment to AR target genes such as to the PSA promoter. It is suggested that STAT3 pathway is essential to drive PCa progression to mCRPC by in part by reactivating the AR pathway [ 136 , 137 ]. In addition, STAT3 activation may promote Enz resistance of CRPC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, STAT3 activation may promote Enz resistance of CRPC. Because of that, inhibition of STAT3 has been an interesting treatment for potential therapy [ 137 , 138 , 139 ]. It was reported that inhibition of STAT3 results in decreased growth of Enz-resistant cells.…”
Section: Introductionmentioning
confidence: 99%